Liquidity trap and expectation dynamics: Fiscal stimulus or fiscal austerity? - Jess Benhabib; George W. Evans; Seppo Honkapohja (Bank of Finland, 2012)
We examine global dynamics under infinite-horizon learning in New Keynesian models where the interest-rate rule is subject to the zero lower bound. As in Evans, Guse and Honkapohja (2008), the intended steady state is locally but not globally stable. Unstable deflationary paths emerge after large pessimistic shocks to expectations. For large expectation shocks that push interest rates to the zero bound, a temporary fiscal stimulus or a policy of fiscal austerity, appropriately tailored in magnitude and duration, will insulate the economy from deflation traps. However "fiscal switching rules" that automatically kick in without discretionary fine tuning can be equally effective.
URN:NBN:fi:bof-20140807527
Keywords: E63; E52; E58; 330; Adaptive Learning; Monetary Policy; Fiscal Policy; Zero Interest Rate Lower Bound